(untitled) (Research, Society and Development, 2021)
As a result of the Covid-19 pandemic, PET-Saúde / Interprofessionality reorganized its work process, acting remotely with the use of Information and Communication Technologies (ICT), fulfilling the criteria of social distance and commitment to public health. Therefore, this article sought to highlight the collaborative skills developed with the use of ICT in a pandemic period by PET-Saúde / Interprofessionality. This is an experience report, of a descriptive type and with a qualitative approach, developed in the municipality of Sobral, Ceará, Brazil, from April to October 2020. Through technological resources it was possible to develop skills relevant to teaching, research and extension. From this perspective, it can be reported that collaborative competences: collaborative leadership, interprofessional communication, team functioning, conflict resolution, community-centered care and clarity of roles were incorporated into this process. Thus, ICT allowed the continuity of PET-Saúde / Interprofessional work processes and activities within the scope of the teaching, research and extension tripod, in order to contribute to facing the pandemic and sustainability of teaching-service-community integration.